Evaluation of the Relationship Between Advanced Oxidation end Products and Inflammatory Markers in Maintenance Hemodialysis Patients - Zeki, Aydin; Serhat, Karadag; Savas, Ozturk; Meltem, Gursu; Sami, Uzun; Egemen, Cebeci; Abdullah, Sumnu; Rumeyza, Kazancioglu (Journal of Nephrology Advances, 2019)
Introduction Increased oxidative stress and blunted anti-oxidant mechanisms are important problems in hemodialysis (HD) patients. Reactive oxygen species (ROS) act directly on proteins, leading to the formation of oxidized amino acids. Advanced oxidation protein products (AOPP) are among these substances. Many oxidant substances increase the level of AOPP. Iron is an element with strong oxidant capacity, especially when used intravenously. It is thought that iron treatment further increases the oxidative stress in HD patients. We aimed to investigate the relationship between AOPP and inflammatory status in HD patients. Materials and Methods Patients who were on maintenance HD program without additional co-morbidities and no history of use of intravenous iron within the last two weeks were recruited in the study. The blood samples taken just before the dialysis session were analyzed for AOPP, serum iron, total iron binding capacity (TIBC), ferritin, C-reactive protein (CRP), ß2-microglobulin, fibrinogen, interleukin (IL)-1, IL-6 and tumor necrosis factor-α levels besides routine biochemical measurements and complete blood count. Results The number of patients included in the study was 102 (n: 53 female, %52.0) and the mean age was 47.6±13.9 years. The mean transferrin saturation was 25.4%. AOPP levels, iron use in patients was higher compared to patients who do not use (respectively 2.58±0.19 mmol/l and 2.50 ±0.16mmol/l, p = 0.046). We did not detect statistically significant correlation of AOPP levels with iron parameters and other inflammatory markers. Conclusion The present study showed that intravenous iron therapy does not increase oxidative stress. Although serum AOPP level was higher in patients on intravenous iron treatment, it was not correlated with iron indices and inflammatory markers. So, intravenous iron may exert its oxidant effect free from serum iron indices.
Keywords: Inflammation; oxidative stress; AOPP; interleukin; hemodialysis.